Revitalization of Community Pharmacists: a Review of Regulation and Implementation - Fachriah Syamsuddin; Cecilia Rina Khristanti; Tri Ratna Rejeki; Utami Tri Adiningsih (Journal of Social Research, 2023)
Community pharmacists have implemented standard pharmaceutical practices particularly in procurement and clinical pharmacy. The purposes of this review were describing the role of community pharmacists in safety use of medicine and responses to COVID-19 outbreak urgency. Review of published literature. Practice of Community Pharmacist in Indonesia based on Ministry of Health Regulation. In medicine use, Indonesia has National Medicine Policy since 2006. National Medicine policy will ensure the availability, equality and affordability of medicine including the essential. It guarantees that available medicine will meet standard of safety, efficacy and has good quality. Also, goal of this policy is to enhance rational use of medicine and preventing misuse/ abuse. Indicator of good pharmaceutical services is patient received good quality of medicine, proper information, and prevention of adverse drug reactions (ADRs). Hospital and community pharmacists have implemented Standard of Pharmaceutical Services. Documentation of medicine information and counselling has been reported to Ministry of Health regularly. Many programmes, activities have been conducted to ensure quality of care, including prevention of adverse drug reactions.